Prosperous Life in the Qur'an: Analysis of Surah Quraish from the Viewpoint of Tafsir Maqashidi Abdul Mustaqim - Muhammad Ebin Rajab Sihombing (Yayasan Insan Mulia Bima, 2023)
The Quraysh tribe is one of the most successful tribes in the Qur'an. Therefore, in this article, research will be carried out on how the Quraysh tribe lived so they could have a prosperous life using analysis of maqashidi interpretation. An important aspect of this research is to find out what is meant by a successful life, the interpretation of Surah Quraish and the analysis of the life of the Quraish tribe from the perspective of Abdul Mustaqim's interpretation of Maqashidi which so far has not received attention from researchers. This study uses a qualitative method with a type of literature review. This method collects data from various literature books, articles, websites and other research results. This study found that a prosperous life is living activities, meeting their needs with a sense of security and comfort, and having a place to live. The Quraish tribe was known to be strong, affiliated, solid, and guarding their trust (the Kaaba). This is what makes them respected and get a prosperous life. Thus, learning from the Quraysh tribe, if you want to get a successful, solid life, then always worship Allah; the best thing is to do it in the congregation.